2020
DOI: 10.3102/0002831220911065
|View full text |Cite
|
Sign up to set email alerts
|

From Interpretation to Instructional Practice: A Network Study of Early-Career Teachers’ Sensemaking in the Era of Accountability Pressures and Common Core State Standards

Abstract: Accountability pressures and the Common Core State Standards for Mathematics have created complex demands for educators, especially early-career teachers (ECTs). Analyzing longitudinal data, including the social networks of 119 ECTs, we find that ECTs increase their ambitious mathematics instruction when their network members positively interpret accountability pressures and curricular standards as manifest in standardized tests and evaluation. This estimated effect is net of an ECT’s rich covariates, includin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 127 publications
(184 reference statements)
0
5
0
Order By: Relevance
“…On a micro level, teachers are more likely to act in ways that support reform efforts if they align with their individual beliefs and practices (Coburn, 2001), which includes personal positive sentiment. Also, social network analysis-based research illustrates that teachers' interactions with colleagues influence their behaviors (Coburn, 2001;Frank et al, 2015Frank et al, , 2020Penuel et al, 2013). Micro-level interactions with colleagues could also affect sentiment at a larger scale, in that momentary, positive interactions between colleagues about an ongoing reform could lead to more robust implementation.…”
Section: How Public Sentiment Can Affect the Success Ofmentioning
confidence: 99%
“…On a micro level, teachers are more likely to act in ways that support reform efforts if they align with their individual beliefs and practices (Coburn, 2001), which includes personal positive sentiment. Also, social network analysis-based research illustrates that teachers' interactions with colleagues influence their behaviors (Coburn, 2001;Frank et al, 2015Frank et al, , 2020Penuel et al, 2013). Micro-level interactions with colleagues could also affect sentiment at a larger scale, in that momentary, positive interactions between colleagues about an ongoing reform could lead to more robust implementation.…”
Section: How Public Sentiment Can Affect the Success Ofmentioning
confidence: 99%
“…For example, in a K-12 setting, curricular standards and external accountability pressures create significant demands for educators, often shaping the culture of data use in schools (Frank, Kim, Salloum, Bieda, & Youngs, 2020;Farrell & Marsh, 2016). Teachers and coaches are expected to make sense of instructional data to set classroom goals, track student progress, re-design a course, or identify new pedagogical strategies, among other tasks (Farrell & Marsh, 2016).…”
Section: Data Sensemaking In K-12 Schoolsmentioning
confidence: 99%
“…For example, in studying the institutional influence of reading policy on teaching practices, Penuel et al (2013) found that teacher practices did not conform to the new normative regime but were shaped by the local norms of practices in collegial subgroups. Other work has described similar relationships with informal social networks and communities of practice shaping how teachers experience institutional forces related to accountability and standards (e.g., Daly & Finnigan, 2010;Diamond & Spillane, 2004;Frank et al, 2020;Wilhelm et al, 2016). Furthermore, intraorganizational teacher social networks serve as a primary context for internalizing the identities, goals, habits, and schemas associated with different logics and shaping how teachers understand which of those available aspects are applicable in a given situation (Bridwell-Mitchell & Sherer, 2017).…”
Section: Network and Filteringmentioning
confidence: 92%